2010
DOI: 10.5155/eurjchem.1.1.54-60.2
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Diazabicyclo[2.2.2]octane (DABCO) as a useful catalyst in organic synthesis

Abstract: KEYWORDS1,4-diazabicyclo[2.2.2]octane (DABCO) has been used in many organic preparations as a good solid catalyst. DABCO has received considerable attention as an inexpensive, ecofriendly, high reactive, easy to handle and non-toxic base catalyst for various organic transformations, affording the corresponding products in excellent yields with high selectivity. In this review, some applications of this catalyst in organic reactions were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…The maximum width of CNT was at the tip of. In contrast, the base was substantially narrower and is consistent with observations of O'Byrne et al who reported a similar phenomenon in nitrogen-doped CNT synthesized from nitrogenated precursors [23,24]. HRTEM of the CNT at the tip exhibited in Figure 1f indicates presence of highly graphitized inner 22-24 walls, whereas the outermost 3-4 walls were comparatively less graphitized, disordered with interstitial defects, which can be attributed to the 'knock-on effect' of microwave radiation, which can damage and dislodge a carbon atom from the walls of CNT [25].…”
Section: Resultssupporting
confidence: 91%
“…The maximum width of CNT was at the tip of. In contrast, the base was substantially narrower and is consistent with observations of O'Byrne et al who reported a similar phenomenon in nitrogen-doped CNT synthesized from nitrogenated precursors [23,24]. HRTEM of the CNT at the tip exhibited in Figure 1f indicates presence of highly graphitized inner 22-24 walls, whereas the outermost 3-4 walls were comparatively less graphitized, disordered with interstitial defects, which can be attributed to the 'knock-on effect' of microwave radiation, which can damage and dislodge a carbon atom from the walls of CNT [25].…”
Section: Resultssupporting
confidence: 91%
“…A polyol crosslinker and an amine catalyst were selected for their low toxicity and low vapor pressure to ensure long shelf-life stability. Specifically, glycerol is a hydrophilic trifunctional alcohol that has been shown to be a strong crosslinker in polyurethanes by ensuring high crosslinking density for the final polyurethane adhesive, while DABCO is a nontoxic, inexpensive catalyst that is highly reactive with isocyanates. , Solubilizing DABCO in glycerol yields a viscous, hydrophilic solution that is not miscible in heavy mineral oil, the chosen hydrophobic phase. Stabilizing an emulsion between DABCO/glycerol and heavy mineral oil required finding an inorganic emulsifying agent that decreased permeability and increased rigidity, as it was key to have shells that were resistant to mixing forces during fabrication but sensitive to shearing forces for deployment .…”
Section: Resultsmentioning
confidence: 99%
“…DABCO is often used as a base in organic synthesis [16] and is a useful synthon for supramolecular architectures [17] . DABCO forms strong halogen bonds as compared to other neutral bases, owing to the rigid pyramidal shape around the N‐atom.…”
Section: Resultsmentioning
confidence: 99%